Contribution of rainwater to the irrigation requirement for paddy cultivation at Tanore Upazila in Rajshahi, Bangladesh - Hasan, Md Rashidul; Nuruzzaman, Md; Al-Mamun, Abdullah (SAGE Publications Ltd, 2019)
Groundwater extraction for irrigation in Bangladesh has caused groundwater depletion, especially in the Northern region. As such, shifting reliance from groundwater to surface water is one of the solutions to mitigate this problem. This study aims at investigating the contribution of effective rainfall to the total consumptive use requirement of rice cultivated in Tanore, Rajshahi, in Bangladesh. The prospect of rainwater harvesting using ponds and its contribution to the consumptive use requirement of rice was also determined. Effective rainfall, temperature, monthly percentage of bright sunshine hours, and consumptive use factor for rice data were collected from Bangladesh Meteorological Department (BMD) and Barind Multipurpose Development Authority (BMDA). Blaney-Criddle method was used to calculate total consumptive use requirement of rice. Analysis results showed that from June to September, there is no requirement of irrigation due to high rainfall in this period. It was revealed that total consumptive use requirement of rice in Tanore averaged at 436millionm3 of water between the period of 2005 and 2012. Effective rainfall contributed to about 38% of the total consumptive use in this period. It was also found that another 5% of the total consumptive use requirement could be supplied by rainwater harvesting using the ponds of Tanore.